RECONCEPTUALIZING SOFTWARE DEVELOPMENT. - Finkelstein, Anthony (Computer (00189162), 2009)
The article discusses the need for radical reconceptualization of software development. It notes that this change requires rethinking the whole concept of design time, deploy time and runtime. Users and their changing and reshaping needs and goals should be the focus of such a reconceptualization. It also cites the importance of software models@run.time as a key step in understanding and dealing with the issues concerning the radical changes.